2020
DOI: 10.3390/min10060510
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer-Confined Cu(II) Complex as an Efficient and Long-Lasting Catalyst for Oxidation of H2S on Montmorillonite

Abstract: Removal of highly toxic H2S for pollution control and operational safety is a pressing need. For this purpose, a montmorillonite intercalated with Cu(II)-phenanthroline complex [Cu[(Phen)(H2O)2]2+ (Mt-CuPhen) was prepared to capture gaseous H2S under mild conditions. This hybrid material was simple to obtain and demonstrated an outstanding ability to entrap H2S at room temperature, retaining high efficiency for a very long time (up to 36.8 g of S/100 g Mt-CuPhen after 3 months of exposure). Sorbent and H2S upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In previous studies [24,25] it was found that the coordination chemistry of the "active" capturing cation -copper(II) in our case -drives the immobilization properties of the whole material: a proper solid functionalized with a Cu(II) complex, effective in the removal of gaseous NH 3 , can successfully work also for the immobilization of heptanethiol and H 2 S, taking advantage of the strong affinity of Cu(II) to both N and S centers. In some cases, the affinity of a metal ion for a gas species is retained also changing the host material.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies [24,25] it was found that the coordination chemistry of the "active" capturing cation -copper(II) in our case -drives the immobilization properties of the whole material: a proper solid functionalized with a Cu(II) complex, effective in the removal of gaseous NH 3 , can successfully work also for the immobilization of heptanethiol and H 2 S, taking advantage of the strong affinity of Cu(II) to both N and S centers. In some cases, the affinity of a metal ion for a gas species is retained also changing the host material.…”
Section: Discussionmentioning
confidence: 67%
“…Besides, HCMs obtained adsorbing Fe +3 Phen on sepiolite demonstrated a better trapping ability toward thiols than montmorillonite, even if the efficiency of this catalytic process was significantly affected by the structural features of this modulated 2:1 layer silicate. Similarly, high trapping ability toward hydrogen sulfide and ammonia gas was observed also for montmorillonite-based HCMs obtained by intercalation of the Cu 2+ -phenanthroline complex. , Furthermore, the Cu 2+ -phenanthroline complexed montmorillonite, after being used for trapping volatile thiol, can be successfully reused to capture aromatic halobenzenes from the gas phase …”
Section: Introductionmentioning
confidence: 76%
“…Similarly, high trapping ability toward hydrogen sulfide and ammonia gas was observed also for montmorillonite-based HCMs obtained by intercalation of the Cu 2+ -phenanthroline complex. 43,44 Furthermore, the Cu 2+phenanthroline complexed montmorillonite, after being used for trapping volatile thiol, can be successfully reused to capture aromatic halobenzenes from the gas phase. 45 The use of natural or modified kaolin (a kaolinite rich clay) as a possible trap for sulfur-bearing gas was rarely considered in the past.…”
Section: Introductionmentioning
confidence: 99%
“…A montmorillonite intercalated with Cu(II)-phenanthroline complex was prepared by Castellini et al to capture gaseous H 2 S under mild conditions. The capture was studied over time and a mechanism of action was proposed by mass spectrometry evolved gas analysis [ 272 ].…”
Section: Applications To Sulfurmentioning
confidence: 99%